2007
DOI: 10.1177/1077558707304644
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Organ Donation Decisions by African Americans

Abstract: The purpose of this article is to review the literature from 1980 to 2005 regarding organ donation decision making by African Americans for themselves and their loved ones and recommend improvements in subsequent studies. Using the behavioral model of health services utilization as an organizing framework, the review procedure consists of a (1) search of health and medical literature using several key words and eight indexes, (2) selection of articles based on specific criteria, and (3) review of each article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…(3) At the same time, African Americans are significantly over represented on the transplant waitlist. For example, African Americans make up 26.5% of the Alabama population,(4) yet comprise 67.6% (2244/3320) of the renal transplant waiting list at the University of Alabama at Birmingham (UAB).…”
Section: Introductionmentioning
confidence: 99%
“…(3) At the same time, African Americans are significantly over represented on the transplant waitlist. For example, African Americans make up 26.5% of the Alabama population,(4) yet comprise 67.6% (2244/3320) of the renal transplant waiting list at the University of Alabama at Birmingham (UAB).…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that minorities are underrepresented in the donor pool (18,(28)(29)(30)(31)(32). However, based on our initial analysis, it does not appear that African Americans who are screened via the web-based application are being excluded more often than white candidates because of body mass index, hypertension or diabetes.…”
Section: Discussionmentioning
confidence: 68%
“…Although minorities are not being excluded at a different rate after they contact the transplant center, it is likely that a substantial proportion of minorities are appropriate candidates but fail to initiate contact (8,18,33). One reported explanation is that minorities fail to even initiate or complete the donor process because they have preconceived fears or attitudes toward donation (32)(33)(34)(35)(36)(37). The web-based tool could be used to combine educational information or support tools with the survey to help allay any fears or misconceptions that prevent donation (13,38).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is compelling evidence that religious beliefs and misperceptions serve as prominent barriers to organ and tissue donation registration among many African Americans (6,26). However, it is not generally understood that most major religions support organ donation (27).…”
mentioning
confidence: 99%
“…This underrepresentation of African Americans in the donor pool speaks to the necessity of greater commitment to organ and tissue donation among African Americans (5). However, numerous barriers exist, and negative attitudes toward donation play a prominent role in the lack of donor registration (6,7). In this issue of CJASN, Locke et al identify and prioritize strategies for increasing organ donation willingness and ultimately donor rates among African Americans (8).…”
mentioning
confidence: 99%